X-ray spectra, light curves and SEDs of blazars frequently observed by Swift. Issue 4 (28th August 2021) - Giommi, Paolo; Perri, M; Capalbi, M; D'Elia, V; Barres de Almeida, U; Brandt, C H; Pollock, A M T; Arneodo, F; Di Giovanni, A; Chang, Y L; Civitarese, O; De Angelis, M; et al.
ABSTRACT: Blazars research is one of the hot topics of contemporary extragalactic astrophysics. That is because these sources are the most abundant type of extragalactic γ-ray sources and are suspected to play a central role in multimessenger astrophysics. We have used Swift_ xrtproc, a tool to carry out an accurate spectral and photometric analysis of the Swift-XRT data of all blazars observed by Swift at least 50 times between December 2004 and the end of 2020. We present a database of X-ray spectra, best-fit parameter values, count rates and flux estimations in several energy bands of over 31 000 X-ray observations and single snapshots of 65 blazars. The results of the X-ray analysis have been combined with other multifrequency archival data to assemble the broad-band Spectral Energy Distributions (SEDs) and the long-term light curves of all sources in the sample. Our study shows that large X-ray luminosity variability on different time-scales is present in all objects. Spectral changes are also frequently observed with a 'harder-when-brighter' or 'softer-when-brighter' behaviour depending on the SED type of the blazars. The peak energy of the synchrotron component (νpeak ) in the SED of HBL blazars, estimated from the log-parabolic shape of their X-ray spectra, also exhibits very large changes in the same source, spanning a range of over two orders of magnitude in Mrk421 and Mrk501, the objects with the best data sets in our sample.